Enhancing Student Engagement and Motivation in Science Using the Flip-J Strategy - Jasmine A. Diata Cruz; Lovelyn A. Calixtro; Jan Jericho C. Batinga; Andre Maverick D. Balila; Hannah Abigail P. Mamuad; James Marlo A. Antonio (Universal Journal of Educational Research, 2024)
Motivation and engagement are critical components of student learning, particularly in the achievement of science learning outcomes. This study aimed to determine the effect of combining flip and jigsaw (Flip-J) learning strategies on students' motivation and engagement in science and to determine the perception of students and the teacher on the use of Flip-J as a learning strategy in science. The participants of the study were 68 Grade 10 students at the Mariano Marcos State University Laboratory High School Laoag who had classes utilizing the Flip-J strategy. The study made use of survey questionnaires on students’ engagement, motivation, and perception of the use of the Flip-J strategy, and teacher’s observation and feedback questionnaires in gathering the needed data. The results gathered from the survey were analyzed using weighted mean, z-test, and Cohen’s d. The findings show that there is a significant improvement in the motivation and engagement of the students after using the Flip-J strategy. Students’ and the teacher observer’s responses to open-ended questions revealed that the Flip-J strategy promotes positive interdependence, encourages proactive learning among students, and improves students' interpersonal skills. Therefore, Flip-J is an effective strategy in enhancing student engagement and motivation in science.